Novel aqueous rechargeable nickel-bismuth batteries based on porous Bi2MoO6 microspheres and CoxNi1-xMoO4@NiCo-layered double hydroxide heterostructure nanoarrays. (December 2020) - Kang, W.; Kong, X.; Li, J.; Wang, P.; Sun, Y.; Zhang, X.; Yang, H.; Lin, B.
Abstract: Aqueous rechargeable batteries represent one promising candidate for new energy storage and conversion systems because of their good safety, low cost, high energy density based on Faradic reactions, and high power density originated from the high ionic conductivity of aqueous electrolyte. Herein, a novel aqueous rechargeable nickel-bismuth battery was developed with highly porous Bi2 MoO6 microspheres as anode active materials and delicately designed binder-free Co0.5 Ni0.5 MoO4 @NiCo-layered double hydroxide heterostructure nanoarrays as the cathode for the first time. The Bi2 MoO6 anode active materials exhibit outstanding electrochemical performances (such as high capacity of 163.2 mAh/g at 1 A/g and superior rate capability of 79.6% at 15 A/g) owing to their porous structure. To obtain the improved cathode, substitution of Co for Ni species of CoX Ni1-X MoO4 as 'core' materials and growing time of NiCo-layered double hydroxide onto the 'core' materials were optimized systematically. The optimal cathode (Co0.5 Ni0.5 MoO4 @NCLDH-12) affords appreciably enhanced electrochemical performances with the high capacity of 386.7 mAh/g at 1 A/g and good rate capability of 64.9% at 15 A/g owing to its advantages in composition and architecture. Desirably, the nickel-bismuth battery can deliver the acceptable maximum energy density of 41.5 W h/kg and power density of 3896.2 W/kg, respectively. The excellent electrochemical performances can be put down to the elaborate architectures of electrodes and synergistic effect between active materials. This current research would enrich the chemistry systems of present aqueous rechargeable batteries and also pave the way to effectively construct promising electrode active materials for aqueous rechargeable nickel-bismuth batteries. Graphical abstract: Image 1 Highlights: Highly porous Bi2 MoO6 microspheres were prepared as anode active materials. Delicately designed binder-free Co0.5 Ni0.5 MoO4 @NCLDH-y grown on nickel foam were synthesized as the cathode. A novel aqueous rechargeable nickel-bismuth battery was developed with Bi2 MoO6 microspheres as anode active materials and Co0.5 Ni0.5 MoO4 @NCLDH-12 as the cathode.